2015
DOI: 10.1038/eye.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Intra-silicone oil injection of methotrexate at the end of vitrectomy for advanced proliferative diabetic retinopathy

Abstract: Purpose To evaluate the role of methotrexate (MTX) injected into the silicone oil at the end of pars plana vitrectomy for advanced proliferative diabetic retinopathy (PDR). Methods In this prospective comparative interventional study, eyes with severe diabetic tractional macular detachment or combined tractional/rhegmatogenous retinal detachment were included. Standard 20 gauge pars plana vitrectomy, and retinal reattachment was performed. In the case group, 250 μg MTX was injected into the silicone oil at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
13
2
Order By: Relevance
“…We hypothesize that IMI might be an effective adjuvant to reduce PVR incidence even among eyes without a history of PVR. While a recent report found that addition of MTX to the silicone oil tamponade after retina reattachment did not prevent recurrent detachment in diabetic retinopathy, 14 the MTX concentrations used were lower than this study and the method of MTX application may limit the access of the drug to the retina. Also, the ability of MTX to induce remission in uveitis suggests that the drug could be particularly efficacious in PVR associated with ocular inflammation.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…We hypothesize that IMI might be an effective adjuvant to reduce PVR incidence even among eyes without a history of PVR. While a recent report found that addition of MTX to the silicone oil tamponade after retina reattachment did not prevent recurrent detachment in diabetic retinopathy, 14 the MTX concentrations used were lower than this study and the method of MTX application may limit the access of the drug to the retina. Also, the ability of MTX to induce remission in uveitis suggests that the drug could be particularly efficacious in PVR associated with ocular inflammation.…”
Section: Discussioncontrasting
confidence: 74%
“…A recent report included 250 µg of MTX in the silicon oil tamponade instilled at the end of retinal reattachment surgery in advanced diabetic retinopathy patients without significant adverse effects; however, clinical efficacy in preventing recurrent RD in diabetic retinopathy was not observed. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Ghasemi Falavarjani et al injected a single dose of MTX (250 µg) into 19 silicone oil filled eyes undergoing repair of a diabetic tractional or combined rhegmatogenous retinal detachment and 19 matched control eyes. The single injection of MTX did not reduce the rate of PVR-induced recurrent RD in this study 4…”
Section: Introductioncontrasting
confidence: 72%
“…Silicone oil is used to treat complex vitreoretinal diseases such as proliferative diabetic retinopathy, retinal detachment, and severe eye trauma [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%